The Soluble Form of Toll-Like Receptor 2 Is Elevated in Serum of Multiple Sclerosis Patients: A Novel Potential Disease Biomarker - Hossain, Md Jakir; Morandi, Elena; Tanasescu, Radu; Frakich, Nanci; Caldano, Marzia; Onion, David; Faraj, Tola A.; Erridge, Clett; Gran, Bruno (Frontiers in Immunology, 2018)
Multiple sclerosis (MS) is an immune-mediated inflammatory demyelinating disease of the central nervous system. It was previously shown that Toll-like receptor (TLR)-2 signalling plays a key role in the murine experimental autoimmune encephalomyelitis (EAE) model of MS, and that TLR2-stimulation of regulatory T cells (Tregs) promotes their conversion to T helper 17 (Th17) cells. Here, we sought potential sources of TLR2 stimulation and evidence of TLR2 activity in MS patient clinical samples. Soluble TLR2 (sTLR2) was found to be significantly elevated in sera of MS patients (n=21), in both relapse and remission, compared to healthy controls (HC) (n=24). This was not associated with the acute phase reaction (APR) as measured by serum C-reactive protein (CRP) level, which was similarly increased in MS patients compared to controls. An independent validation cohort from a different ethnic background showed a similar upward trend in mean sTLR2 values in relapsing-remitting MS (RRMS) patients, and significant differences in sTLR2 values between patients and healthy controls were preserved when the data from the two cohorts were pooled together (n=41 RRMS and 44 HC, P=0.0006). TLR2-stimulants, measured using a human embryonic kidney (HEK-293) cell transfectant reporter assay, were significantly higher in urine of MS patients than healthy controls. A screen of several common urinary tract infections (UTI)-related organisms showed strong induction of TLR2-signalling in the same assay. Taken together, these results indicate that two different markers of TLR2-activity - urinary TLR2-stimulants, and serum sTLR2 levels - are significantly elevated in MS patients compared to healthy controls.